A Histological Comparison of Two Human Acellular Dermal Matrix Products in Prosthetic-Based Breast Reconstruction. Issue 12 (December 2017) - Moyer, Hunter R.; Hart, Alexandra M.; Yeager, Jessica; Losken, Albert
Abstract : Background: Acellular dermal matrices (ADMs) are an integral component of breast reconstruction. The ideal matrix would be relatively immuno-inert, allow rapid vascularization, and be affordable. The purpose of this study was to histologically compare 2 commonly used ADM products. Methods: This is a prospective histological study of 17 patients (20 breasts) following prosthetic-based breast reconstruction with ADM: Alloderm (LifeCell Corp, Branchburg, N.J.) or Cortiva (RTI Surgical, Alachua Fla.). Biopsies were taken from the dermal matrix and natural capsules surrounding the expander/implant during secondary surgery [Range, 72—694 days (mean, 217 days)]. Biopsy specimens were prepared via hematoxylin and eosin, Masson's trichrome, elastin, and transforming growth factor (TGF)-1 stains. Quantitative analysis of staining was performed with ImageJ software. The clinical outcome of each patient is analyzed in relation to capsule architecture and ADM performance. Results: There were 7 breasts in the Alloderm group and 13 in the Cortiva group. Both groups had similar demographic, aesthetic results, and complication profiles. The TGF-1 staining demonstrated significantly lower levels in the Cortiva capsules ( P = 0.0139). The percentage of elastin and collagen are similar in the Cortiva, Alloderm, and natural peri-implant capsules. The native capsules show a significantly greater number of blood vessels when compared with Cortiva and Alloderm ( P = 0.0371 and P = 0.0347, respectively); however, there is no difference in vascular pattern between the 2 dermal matrices. Discussion: Postoperatively, Cortiva demonstrates equal vascularity with less TGF-1 activation compared with Alloderm. The clinical success and complication profile were similar between the Alloderm and Cortiva patients.